Analisis Kesulitan Belajar Siswa Pada Materi Struktur Atom - Neti Afrianis; Laura Ningsih (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2022)
This research aimed at analyzing student learning difficulty in answering chemistry questions on Atomic Structure lessonat the tenth grade of State Senior High School 12 Pekanbaru.  It was a qualitative descriptive research.  20 test items and interview to 35 students were the techniques of collecting the data.  P= b/n×100 % formula was used to analyze the data.  The analysis result showed that students experiencing learning difficulty about the concept were 59.73% and 74.91% in calculation.  Interview result showed that the lack of student comprehension in understanding the concept and calculation on Atomic Structure lesson, the use of formula in answering questions that was often wrong, teacher's habit in learning chemistry that was writing on the whiteboardonly, and the students who were lack of anxiety in answering examples of questions given by the teachers.  So, it could be concluded that there were learning difficultieson Atomic Structure lesson of Chemistry subjectat the tenth grade of MIPA at State Senior High School 12 Pekanbaru.